Multi-electron excitation contributions towards primary and satellite states in the photoelectron spectrum. Issue 14 (24th March 2022) - Moitra, Torsha; Paul, Alexander C.; Decleva, Piero; Koch, Henrik; Coriani, Sonia
Abstract : The computation of Dyson orbitals and corresponding ionization energies has been implemented within the equation of motion coupled cluster singles, doubles and perturbative triples (EOM-CC3) method. Abstract : The computation of Dyson orbitals and corresponding ionization energies has been implemented within the equation of motion coupled cluster singles, doubles and perturbative triples (EOM-CC3) method. Coupled to an accurate description of the electronic continuum via a time-dependent density functional approach using a multicentric B-spline basis, this yields highly accurate photoionization dynamical parameters (cross-sections, branching ratios, asymmetry parameters and dichroic coefficients) for primary (1h) states as well as satellite states of (2h1p) character. Illustrative results are presented for the molecular systems H2 O, H2 S, CS, CS2 and ( S )-propylene oxide (a.k.a. methyloxirane).